Anybody shining - Dowell, Frances O'Roark. (New York : Atheneum Books for Young Readers, 2014)
In a series of letters to her cousin, twelve-year-old Arie Mae relates her life in a mountain valley of North Carolina in the 1920s.
Keywords: Mountain life -- North Carolina -- Fiction; North Carolina -- History -- 20th century -- Fiction; Letters -- Fiction; Epistolary fiction -- Juvenile